الشيخ المحدِّث أبو جابر عبد الله الليبي وجهوده الإصلاحية والدعوية في ماليزيا - Rohaizan, Baru; Mohamed Fathy, Mohamed Abdelgelil; Gahit Khalid, Abdusalam; AlFaadhli Mwadah, Ibrahim (2018)
Sheikh Abu Jaber Abdullah al-Liby is one of the scientists of the Islamic Maghreb who came to Malaysia and performed the mission for which they leave for it. This scientist came to Malaysia at the invitation of Sheikh al-Hadi, principal of the al-Mashoor School in Pinang Island, in order to raise the level of Arabic schools performance there. Those who are interested in having deeper knowledge about the efforts of Libyan scientists can get their desire fully satisfied about the knowledge of Sheikh Abu Jaber al-Ghadamesi and discover his advocacy and reform works in Malaysia only after a great effort. Therefore, this article is conducted in order to interduce Al Sheikh Abu Jaber and highlight his reform efforts, his main contribution in developing the science in Malaysia, how to get benefit from the efforts of his advocacy and reform works the scholars of the Sunnis in resisting them and to analyse his efforts' outcomes of his mission, applying them to ours current situations. This article concludes by saying that Sheikh Abu Jaber had done the mission geniusly for which he came for particularly in this island and the in the rest regions in malaysian country generally. He reformed the teaching methods and study programs at this school, and used the wisdom and interpretation. He also builds and funded schools and spread learning Arabic language all over that region. More importantly, he encouraged students and helped them to memorize and recite the Holy Quran and intonation it. He made a contributing work by correcting the common mispronunciation which non-native Muslim speakers used to produce at this region. He repaired and rebookbinded damaged holy book (al-Quran) therefore, due to his efforts, education in Malaysia had magnificently developed and changes in terms of curriculum design and performance in accordance to the curricula used in Makkah. As a result of this, schools have become doing their mission effectively, and was able to achieve widespread fame.